PENGARUH WAKTU PEMASAKAN DAN VOLUME LARUTAN PEMASAK TERHADAP VISKOSITAS PULP DARI AMPAS TEBU - Rizkia Arliani (Jurnal Ilmu Teknik, 2012)
Bagasse contains cellulose a fairly high, so it can be used as alternative raw materials pulping. Process pulping used in this study is acetosolv process, which is releasing fibers of bagasse with acetic acid solution. This study looked at the effect of cooking time and cooking solution volume of % yield and viscosity of the pulp produced. Range of variables used in this study is the cooking time 90, 120, 150, and 180 minutes with a volume of a solution of acetic acid cookers 100, 120, 140 and 160. The results were analyzed to obtain quality pulp viscosity and % yield. Pulp obtained best results when cooking 90 minutes, with the volume of a solution of 100 ml of acetic acid cooker.